1989
DOI: 10.1007/bf01855006
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of amino acids in protective solutions to postischemic functional recovery of canine kidneys

Abstract: Amino acids are known to increase glomerular filtration rate (GFR). There is also an early resumption of filtration following 2-h renal ischemic stress under protection by histidine-buffered histidine-tryptophan-ketoglutarate solution (HTK), possibly due in part to an amino acid effect. Hence, we have examined the possibility of further enhancing the postischemic GFR by adding 32 (ASP I; 4 mM Mg2+) or 36 (ASP II; 6 mM Mg2+) mM L-aspartate (asp) or 32 mM DL-aspartate (ASP III) to the HTK solution in place of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 63 publications
(79 reference statements)
0
12
0
Order By: Relevance
“…It has been shown that the exchange of the Na+-, K+-and M$+-chloride in the HTK-solution by the corresponding salts of L-aspartic acid leads to a distinctly higher GFR and higher transport rates in the early phase of postischaemic recovery after 2 h of ischaemia. With an extra 2 mM Mg2+ in addition to a solution modification with Laspartate, an even higher GFR was reached [3]. However, contrary to the HTK groups with different ischaemia times, this higher GFR with aspartate solutions did not increase, in the case of 6 mM Mg2+ (Asp 11) it even slightly decreased the renal ATP content compared to HTK kidneys with a comparable ischaemic stress (Fig.…”
Section: I4 -mentioning
confidence: 85%
See 4 more Smart Citations
“…It has been shown that the exchange of the Na+-, K+-and M$+-chloride in the HTK-solution by the corresponding salts of L-aspartic acid leads to a distinctly higher GFR and higher transport rates in the early phase of postischaemic recovery after 2 h of ischaemia. With an extra 2 mM Mg2+ in addition to a solution modification with Laspartate, an even higher GFR was reached [3]. However, contrary to the HTK groups with different ischaemia times, this higher GFR with aspartate solutions did not increase, in the case of 6 mM Mg2+ (Asp 11) it even slightly decreased the renal ATP content compared to HTK kidneys with a comparable ischaemic stress (Fig.…”
Section: I4 -mentioning
confidence: 85%
“…Since aspartate especially after ischaemia is a good renal substrate, aspartate metabolism could have mediated the effects [3]. However, a relevant SAN elevation by an enhanced synthesis of purine nucleotides by aspartate was not detectable (Fig.…”
Section: I4 -mentioning
confidence: 97%
See 3 more Smart Citations